2018
DOI: 10.1016/j.nano.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of iron oxide nanoparticles and iron-based complex drug formulations: Therapeutic benefits, toxicity, mechanistic insights, and translational considerations

Abstract: Nanotechnology offers several advantages for drug delivery. However, there is the need for addressing potential safety concerns regarding the adverse health effects of these unique materials. Some such effects may occur due to undesirable interactions between nanoparticles and the immune system, and they may include hypersensitivity reactions, immunosuppression, and immunostimulation. While strategies, models, and approaches for studying the immunological safety of various engineered nanoparticles, including m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 167 publications
(200 reference statements)
2
75
0
Order By: Relevance
“…MIONs can mediate toxicity through several mechanisms that all have to be taken into account when evaluating their safety. Most intracellular toxicity is caused by generation of reactive oxygen species whereas in vivo disturbances of blood clotting, iron homeostasis and macrophage function, as well as organ toxicities, are additional considerations (Ilinskaya and Dobrovolskaia, 2013 ; Wu et al, 2014 ; Wei et al, 2016 ; Shah and Dobrovolskaia, 2018 ). A more detailed discussion of MION toxicity can be found in specialized review articles (Reddy et al, 2012 ; Liu et al, 2013 ; Arami et al, 2015 ).…”
Section: Dosing and Toxicity Of Magnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…MIONs can mediate toxicity through several mechanisms that all have to be taken into account when evaluating their safety. Most intracellular toxicity is caused by generation of reactive oxygen species whereas in vivo disturbances of blood clotting, iron homeostasis and macrophage function, as well as organ toxicities, are additional considerations (Ilinskaya and Dobrovolskaia, 2013 ; Wu et al, 2014 ; Wei et al, 2016 ; Shah and Dobrovolskaia, 2018 ). A more detailed discussion of MION toxicity can be found in specialized review articles (Reddy et al, 2012 ; Liu et al, 2013 ; Arami et al, 2015 ).…”
Section: Dosing and Toxicity Of Magnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…In general, MNPs do not cause notable toxicity in different immune cell types, with high cell viability percentages often observed [86]. MNP toxicity usually occurs mainly when high doses and prolonged exposure times are used [87,88] or in the presence of certain coatings [89]. Besides, there are several studies demonstrating the low toxicity of MNPs in both human and murine T and NK cell lines and in primary T and NK cells [75,78,80,[89][90][91][92][93][94][95][96][97][98][99].…”
Section: The Interaction Between Mnps and Lymphoid Cellsmentioning
confidence: 99%
“…34 Production of reactive oxygen species can be induced by nano-materials as nanomaterials are able to reach mitochondria and hence may induce inammatory response in activated macrophages. 35 Microarray analysis revealed that gene responsible for oxidative stress and inammatory responses undergo for reprogramming in IONPs treated mouse macrophages. 36 We therefore speculate that IONPs-induced ROS activates NF-kB, which subsequently leads to release of pro-inammatory cytokines.…”
Section: Measurement Of Serum Cytokinesmentioning
confidence: 99%